Pemberdayaan Masyarakat Desa Kuala Bhee Melalui Pelatihan Pembuatan Sabun Cuci Piring Untuk Pengembangkan Produk UMKM - ARRAZY ELBA RIDHA; Dewi Andriani; Rika Rahma Sundari; Azzamsyah Ali; Miftahurrahmi Suandra (Jurnal Pengabdian Agro and Marine Industry, 2026)
The Community Service Program in Kuala Bhee Village, Woyla District, West Aceh Regency, aims to empower the community through training in dish soap production. This program is motivated by the human resource potential in the village and the community's desire to improve economic welfare through the development of Micro, Small, and Medium Enterprises (MSMEs), despite facing limitations in product innovation and access to entrepreneurship training. The methodology of the activity included field surveys to identify problems of dependence on products from outside the village, socialization of the importance of MSMEs and the benefits of training, as well as hands-on practice in making dishwashing soap. The soap-making process was taught in detail, from the introduction of raw materials to mixing and packaging techniques. The results of this activity show that participants are now able to identify important ingredients and understand the production process, and some participants have shown enthusiasm and interest in turning dish soap making into a new business opportunity. Thus, this training has succeeded in providing new skills, opening up insights into business opportunities, and increasing the economic independence of the Kuala Bhee Village community.